Bone joint biological super-lubricating copolymer and preparation method thereof
By developing bone joint biosuperlubricating copolymers, the limitations of traditional lubricants in the field of artificial joint and cartilage repair using dopamine methacrylamide and positively charged poly(2-ethyl-2-oxazoline) copolymerization is solved by the development of osteoarthritis biosuperior lubricating copolymers, the use of dopamine methacrylamide and positively charged poly(2-ethyl-2-oxazoline) copolymerization has been solved by the limitations of traditional lubricants in the field of artificial joint and cartilage repair. , achieving efficient joint lubrication and tissue repair effects.
Patent Information
- Application Number
- CN202411590760.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing traditional lubricants have limitations in the field of artificial joint and cartilage repair, and cannot effectively maintain joint lubrication, resulting in the aggravation of the symptoms of arthritis.
A bone joint biosuperlubricated copolymer was developed to form a material with adhesion and excellent hydration lubricating properties by copolymerizing dopamine methacrylamide and positively charged poly(2-ethyl-2-oxazoline). The copolymer can be directly modified on agent microspheres for the treatment of osteoarthritis.
This bio-ultralubricated copolymer can effectively reduce joint surface friction and wear, reduce pain and discomfort in patients with osteoarthritis, promote tissue growth and repair, and significantly improve bone and joint health status.
Smart Images

Figure CN119463045A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and specifically provides a bone and joint biological super-lubricating copolymer and a preparation method thereof. Background Art
[0002] Osteoarthritis is a common chronic joint disease that can cause pain, stiffness, and limited joint function. Osteoarthritis often leads to reduced or disrupted joint lubrication and accelerated wear of joint cartilage. Lubricating fluid in normal joints can reduce friction and wear on the joint surfaces and protect the articular cartilage from damage. However, in people with osteoarthritis, the quality and quantity of lubricating fluid may be impaired, resulting in increased friction between joints and exacerbating arthritis symptoms. Therefore, maintaining good joint lubrication can help slow the progression of osteoarthritis and reduce symptoms.
[0003] In the field of bone and joint health, research on biolubricating materials has attracted much attention. Currently, improving the lubrication performance between osteoarthritis cartilage is mainly achieved by injecting exogenous lubricants such as hyaluronic acid and chitosan into the joint cavity. However, this method requires frequent injections, which will lead to further damage to the articular cartilage and aggravate the progression of the disease.
[0004] Therefore, in view of the limitations of current traditional lubricants in the field of artificial joints and cartilage repair, it is crucial to develop materials with biocompatibility and excellent lubrication properties. Summary of the invention
[0005] The purpose of the present invention is to provide a biological super lubricating copolymer and a preparation method thereof in view of the problems existing in conventional lubricants. The bone and joint biological super lubricating copolymer can be directly modified on the pharmaceutical microspheres and has the characteristics of strong adhesion and excellent hydration lubrication performance.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] The bone joint biological super-lubricating copolymer material comprises dopamine methacrylamide and a positively charged poly (2-ethyl-2-oxazoline) copolymer; the structural formula of the super-lubricating copolymer is shown in the following formula I:
[0008]
[0009] In formula I: x=8~9, y=6~7.
[0010] The preparation process of the bone joint biological super lubricating copolymer is as follows:
[0011]
[0012] In formula II: MeOTs is methyl p-toluenesulfonate, and MA is methacrylic anhydride.
[0013] The preparation method of dopamine methacrylamide is as follows: under nitrogen protection, sodium tetraborate and sodium hydroxide solution are mixed, dopamine hydrochloride is quickly added at room temperature, and a mixed solution of methacrylic anhydride and tetrahydrofuran is dripped into the mixture to carry out a grafting reaction to obtain modified dopamine methacrylamide;
[0014] Among them, the mass ratio of dopamine hydrochloride and sodium tetraborate is 1:(2-5), the volume ratio of methacrylic anhydride and tetrahydrofuran is 1:(2-8), the grafting reaction time is 12-24h, the reaction temperature is 20-30°C, and the pH needs to be controlled at 2-3.
[0015] The preparation method of the positively charged poly (2-ethyl-2-oxazoline) copolymer is as follows: 2-ethyl-2-oxazoline is mixed with an acetonitrile solution, methyl p-toluenesulfonate and N-(3-dimethylaminopropyl) methacrylamide are added for grafting reaction to obtain the positively charged poly (2-ethyl-2-oxazoline).
[0016] The mass ratio of 2-ethyl-2-oxazoline to methyl p-toluenesulfonate is (5-15):1, the molar ratio of methyl p-toluenesulfonate to N-(3-dimethylaminopropyl)methacrylamide is 1:(1-20), the grafting reaction time is 12-24h, and the reaction temperature is 60-80°C.
[0017] The poly(2-ethyl-2-oxazoline) of the present invention has a positive charge, N + The introduction of ions makes the polymer positively charged, which has good advantages in the treatment of osteoarthritis, including: ① Anti-inflammatory effect: Positively charged polymer materials can adsorb and neutralize negatively charged inflammatory mediators, thereby reducing inflammatory reactions and helping to relieve pain and discomfort in patients with osteoarthritis. ② Removal of degradation substances: Positively charged polymers can adsorb and remove degradation products and metabolites in joints, helping to maintain a clean and stable environment in the joints. ③ Promote tissue growth and repair: Positively charged polymers have good cell affinity, can promote the attachment, growth and differentiation of bone and cartilage cells, and are beneficial to tissue repair and regeneration. Moreover, the positively charged polymer is highly hydrophilic, has excellent hydration capacity and lubrication properties, can adhere to the joint surface, absorb surrounding water molecules to form a hydration layer, effectively reduce surface friction and wear, and is copolymerized with dopamine methacrylamide. The unique adhesion properties of dopamine and the phenol structure can effectively remove free radicals and achieve anti-inflammatory effects.
[0018] The modified dopamine methacrylamide and positively charged poly (2-ethyl-2-oxazoline) are mixed with N, N-dimethylformamide solvent and subjected to free radical polymerization reaction to obtain a biological super-lubricating copolymer.
[0019] The mass ratio of dopamine methacrylamide to positively charged poly (2-ethyl-2-oxazoline) is 1: (1-10), the free radical polymerization reaction time is 12-48 hours, and the reaction temperature is 60-80°C.
[0020] After the first step of grafting reaction is completed, the product is extracted, precipitated, and vacuum dried to obtain the final product; after the second step of grafting reaction is completed, the product is precipitated and vacuum dried to obtain the final product; after the third step of free radical polymerization reaction is completed, the product is dialyzed and freeze-dried in turn.
[0021] The present invention also provides a method for preparing a bone joint biological super-lubricating copolymer solution, wherein a copolymer obtained by polymerizing modified dopamine methacrylamide and positively charged poly (2-ethyl-2-oxazoline) is dissolved in the good solvent to obtain a bone joint biological super-lubricating copolymer solution.
[0022] The preferred good solvent is Tris-HCl buffer. The concentration of the bone joint biological super lubricating copolymer in the good solvent is 1-10 mg / mL.
[0023] The invention also provides application of the bone and joint biological super-lubricating copolymer and the copolymer solution in modifying new dosage form microspheres for treating osteoarthritis.
[0024] Another aspect of the present invention:
[0025] The carrier microspheres of the bone joint biological super-lubricating copolymer material are prepared by using a microfluidic device. The preparation method comprises the following steps:
[0026] (1) dissolving methacryloyl gelatin in phosphate buffer to form solution A as a dispersed phase;
[0027] (2) Liquid paraffin is solution B, serving as the continuous phase;
[0028] (3) Based on the microfluidic platform, the flow rates of the continuous phase and the dispersed phase were set, and methacryloyl gelatin (GelMA) was formed into microspheres under UV cross-linking.
[0029] (4) After washing away the excess oil phase on the surface of the microspheres with anhydrous ethanol and PBS, the microspheres were added to the biological super-lubricating copolymer solution and incubated at 37°C in a shaker for 24 h to successfully modify the copolymer on the surface of the microspheres to form lubricating microspheres.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. Dopamine, as an important derivative of dihydroxyphenylalanine, inherits the adhesive properties of mussels and also shows potential in bone and joints. Dopamine methacrylamide (DMA), as a derivative of dopamine, can be combined with other biomedical materials to play a role in repairing cartilage and alleviating diseases such as arthritis, providing a new solution for bone and joint health.
[0032] 2. Poly(2-ethyl-2-oxazoline) (POX) is a highly hydrophilic polymer with excellent hydration ability and lubrication properties. In bone joints, it works through its hydration lubrication mechanism. When POX is attached to the joint surface, it absorbs surrounding water molecules to form a hydration layer, effectively reducing surface friction and wear, thereby providing a lubricating effect. Its lubricating properties can reduce friction between bones and cartilage, relieving pain and discomfort caused by arthritis.
[0033] 3. The positively charged biological superlubricating copolymer material provided by the present invention can adsorb and neutralize negatively charged inflammatory mediators, has good cell affinity, can promote the growth and differentiation of chondrocytes, thereby reducing inflammatory responses, and the presence of its lubrication and adhesion properties effectively reduces the friction of the lubricating microspheres in the joint cavity, helping to alleviate the discomfort of osteoarthritis patients. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The DMA obtained in Example 5 1 H NMR spectra;
[0035] Figure 2 The POX obtained in Example 5 1 H NMR spectra;
[0036] Figure 3 is the DMA-POX obtained in Example 5 1 H NMR spectra;
[0037] Figure 4 This is the Fourier infrared spectrum of DMA obtained in Example 5;
[0038] Figure 5 is the Fourier transform infrared spectrum of POX obtained in Example 5;
[0039] Figure 6 This is the Fourier transform infrared spectrum of DMA-POX obtained in Example 5;
[0040] Figure 7 The Fourier transform infrared spectra of the blank microspheres and lubricating microspheres obtained in Example 6;
[0041] Figure 8The surface charge test results of DMA-POX, GelMA, and GelMA@DMA-POX;
[0042] Fig. 9 The friction coefficient test results of PBS, GelMA, and GelMA@DMA-POX;
[0043] Fig.10 The histological therapeutic effects of PBS, GelMA, and GelMA@DMA-POX on rats with osteoarthritis;
[0044] Fig.11 This is the imaging detection effect of PBS, GelMA, and GelMA@DMA-POX on rats with osteoarthritis. DETAILED DESCRIPTION
[0045] The present invention provides a bone and joint biological super-lubricating copolymer, the structural formula of which is shown in the following formula I:
[0046]
[0047] In the present invention, the x represents the grafting ratio of dopamine methacrylamide, and the y represents the grafting ratio of positively charged poly (2-ethyl-2-oxazoline).
[0048] In the present invention, x is preferably 8-9, and y is preferably 6-7.
[0049] In the present invention, the preparation method of the copolymer of dopamine methacrylamide and positively charged poly (2-ethyl-2-oxazoline) comprises the following steps:
[0050] The present invention mixes sodium tetraborate and sodium hydroxide solution under nitrogen atmosphere, quickly adds dopamine hydrochloride at room temperature, and simultaneously drips a mixed solution of methacrylic acid and tetrahydrofuran to perform a first grafting reaction to obtain dopamine methacrylamide (denoted as DMA). The mass ratio of sodium hydroxide to sodium tetraborate is 1:(2-5), more preferably 1:(2-3), the amount of dopamine hydrochloride added is 2-10g, more preferably 4-6g, the volume ratio of methacrylic anhydride to tetrahydrofuran is 1:(2-8), more preferably 1:(4-6), the temperature of the first grafting reaction is preferably 20-30°C, more preferably 25-28°C, the time of the first grafting reaction is preferably 12-24h, more preferably 18-24h, and the pH at the end of the first grafting reaction needs to be controlled at 2-3, more preferably 2-2.5.
[0051] After the first grafting reaction is completed, the product is extracted, precipitated, and vacuum dried to obtain the final product, dopamine methacrylamide. In the present invention, the product obtained from the first grafting reaction is preferably extracted with ethyl acetate, the drying is preferably done with anhydrous magnesium sulfate, the precipitation is preferably done with petroleum ether, and the vacuum drying time is preferably 12 to 36 hours.
[0052] The present invention mixes 2-ethyl-2-oxazoline with an acetonitrile solution, adds methyl p-toluenesulfonate and N-(3-dimethylaminopropyl)methacrylamide to carry out a second-step grafting reaction, and obtains positively charged poly(2-ethyl-2-oxazoline). The mass ratio of the 2-ethyl-2-oxazoline to the methyl p-toluenesulfonate is (5-15):1, more preferably (8-12):1, and more preferably 10:1; the volume ratio of the 2-ethyl-2-oxazoline to the anhydrous acetonitrile solvent is 1:1, the molar ratio of the methyl p-toluenesulfonate to the N-(3-dimethylaminopropyl)methacrylamide is 1:(1-20), more preferably 1:(4-6), the reaction temperature of the second-step grafting reaction is preferably 60-80°C, more preferably 70-80°C, and the reaction time of the second-step grafting reaction is preferably 12-24h, more preferably 18-24h.
[0053] After the second grafting reaction is completed, the product is precipitated and vacuum dried to obtain the final product, i.e., positively charged poly(2-ethyl-2-oxazoline). The product obtained from the second grafting reaction is preferably precipitated by cold anhydrous ether, and the product is preferably vacuum dried, and the vacuum drying time is preferably 12 to 36 hours.
[0054] After obtaining dopamine methacrylamide and positively charged poly(2-ethyl-2-oxazoline), the modified dopamine methacrylamide and positively charged poly(2-ethyl-2-oxazoline) are dissolved in N,N-dimethylformamide solvent. The preferred mass ratio of dopamine methacrylamide and positively charged poly(2-ethyl-2-oxazoline) is 1:(1-10), and the more preferred mass ratio is 1:(2-4). The amount ratio of the initiator azobisisobutyronitrile to the solvent N,N-dimethylformamide is preferably 1 mg:(1-5) mL, and more preferably 1 mg:(1-3) mL. The temperature of the third step free radical polymerization reaction is preferably 60-80° C., and more preferably 70-80° C. The time of the third step free radical polymerization reaction is preferably 12-48 h, and more preferably 24-48 h. The third step free radical polymerization reaction is preferably carried out under nitrogen protection.
[0055] After the third step of free radical polymerization reaction is completed, the obtained lubricating copolymer (denoted as DMA-POX) is preferably dialyzed and freeze-dried in sequence; the dialysis solvent is preferably deionized water, the molecular weight cutoff of the dialysis bag is preferably 2000-8000 kDa, the dialysis time is preferably 2-5 days, more preferably 3 days; the freeze-drying temperature is preferably -70--80°C, and the freeze-drying time is preferably 12-36 hours.
[0056] The present invention also provides a method for preparing the bone joint super-lubricating copolymer solution described in the above scheme, comprising the following steps: dissolving the copolymer obtained from dopamine methacrylamide and positively charged poly (2-ethyl-2-oxazoline) in the good solvent to obtain a biological super-lubricating solution. The present invention has no specific requirements for the dissolution conditions of the copolymer, and it can be stirred at room temperature until it is completely dissolved.
[0057] In the present invention, the good solvent is preferably Tris-HCl buffer, the pH value of the Tris-HCl buffer is preferably 8-9, and the concentration of the copolymer in the bone and joint super-lubricating copolymer solution is preferably (0.1-10) mg / mL, more preferably (1-8) mg / mL, and further preferably 4 mg / mL.
[0058] The present invention also provides the use of the above-mentioned bone joint super lubricating copolymer solution in preparing a new drug dosage form microsphere for treating osteoarthritis. The method comprises the following steps:
[0059] The bone joint biological super-lubricating copolymer material is dissolved in the good solvent to obtain a super-lubricating solution, and gelatin microspheres are prepared based on microfluidic technology. Preferably, microspheres are added to the super-lubricating solution, and the amount ratio of the microspheres to the super-lubricating solution is preferably (4-10) mg / mL to obtain super-lubricating microspheres. The bone joint biological super-lubricating copolymer solution and super-lubricating microspheres provided by the present invention have good biocompatibility, strong interface adhesion and excellent water lubrication performance, and have excellent application prospects in the treatment of osteoarthritis.
[0060] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0061] Example 1
[0062] Step 1: Under an inert gas atmosphere, add 4g of sodium hydroxide, 10g of sodium tetraborate and 100mL of deionized water to a 250mL three-necked flask to fully dissolve them. At room temperature, quickly add 3g of dopamine hydrochloride, and at the same time, drop a mixed solution of 5mL of methacrylic anhydride and 25mL of tetrahydrofuran into a round-bottom flask, and then adjust the pH value of the solution to 8.5 with sodium hydroxide. At the same time, monitor the pH value of the solution every 2h to control it at 8.5. After reacting at room temperature for 12h, adjust the pH of the reaction mixture to 2 with hydrochloric acid. After the reaction is complete, extract with ethyl acetate, dry with anhydrous magnesium sulfate, precipitate with petroleum ether, and finally obtain a white solid powder, i.e. dopamine methacrylamide DMA, after vacuum drying the product.
[0063] Step 2: Under an inert gas atmosphere, 5 g of 2-ethyl-2-oxazoline, 1 g of methyl p-toluenesulfonate and 40 mL of anhydrous acetonitrile were added to the reaction bottle, placed in an 80°C oil bath, stirred for reaction for 12 h, then cooled to room temperature, 3.5 g of N-(3-dimethylaminopropyl) methacrylamide was added dropwise through a syringe, stirred for reaction at room temperature for 12 h, and the reaction was completed. The excess solvent was removed by a rotary evaporator, and the remaining product was precipitated with anhydrous ether and vacuum dried to obtain the final product, i.e., positively charged poly(2-ethyl-2-oxazoline)POX.
[0064] Step 3: Under an inert gas atmosphere, 0.5 g DMA and 2.0 g POX monomer were dissolved in 10 mL N,N-dimethylformamide (DMF), and 6 mg azobisisobutyronitrile (AIBN) was quickly added as an initiator. Stir at 70 ° C for 24 hours to allow the reaction to occur, and the viscosity change was observed during the reaction. After the reaction, the mixture was dialyzed with deionized water for 3 days and freeze-dried for 1 day to obtain the final product, DMA-POX.
[0065] Example 2
[0066] Step 1: Under an inert gas atmosphere, add 4g of sodium hydroxide, 10g of sodium tetraborate and 100mL of deionized water to a 250mL three-necked flask to fully dissolve them. At room temperature, quickly add 3g of dopamine hydrochloride, and at the same time, drop a mixed solution of 5mL of methacrylic anhydride and 25mL of tetrahydrofuran into a round-bottom flask, and then adjust the pH value of the solution to 8.5 with sodium hydroxide. At the same time, monitor the pH value of the solution every 2h to control it at 8.5. After reacting at room temperature for 12h, adjust the pH of the reaction mixture to 2 with hydrochloric acid. After the reaction is complete, extract with ethyl acetate, dry with anhydrous magnesium sulfate, precipitate with petroleum ether, and finally obtain a white solid powder, i.e. dopamine methacrylamide DMA, after vacuum drying the product.
[0067] Step 2: Under an inert gas atmosphere, 5 g of 2-ethyl-2-oxazoline, 1 g of methyl p-toluenesulfonate and 40 mL of anhydrous acetonitrile were added to the reaction bottle, placed in an 80°C oil bath, stirred for reaction for 12 h, then cooled to room temperature, 4.5 g of N-(3-dimethylaminopropyl) methacrylamide was added dropwise through a syringe, stirred for reaction at room temperature for 12 h, and the reaction was completed. The excess solvent was removed by a rotary evaporator, and the remaining product was precipitated with anhydrous ether and vacuum dried to obtain the final product, i.e., positively charged poly(2-ethyl-2-oxazoline)POX.
[0068] Step 3: Under an inert gas atmosphere, 0.5 g DMA and 2.0 g POX monomer were dissolved in 10 mL N,N-dimethylformamide (DMF), and 6 mg azobisisobutyronitrile (AIBN) was quickly added as an initiator. Stir at 70 ° C for 24 hours to allow the reaction to occur, and the viscosity change was observed during the reaction. After the reaction, the mixture was dialyzed with deionized water for 3 days and freeze-dried for 1 day to obtain the final product, DMA-POX.
[0069] Example 3
[0070] Step 1: Under an inert gas atmosphere, add 4g of sodium hydroxide, 10g of sodium tetraborate and 100mL of deionized water to a 250mL three-necked flask to fully dissolve them. At room temperature, quickly add 3g of dopamine hydrochloride, and at the same time, drop a mixed solution of 5mL of methacrylic anhydride and 25mL of tetrahydrofuran into a round-bottom flask, and then adjust the pH value of the solution to 8.5 with sodium hydroxide. At the same time, monitor the pH value of the solution every 2h to control it at 8.5. After reacting at room temperature for 12h, adjust the pH of the reaction mixture to 2 with hydrochloric acid. After the reaction is complete, extract with ethyl acetate, dry with anhydrous magnesium sulfate, precipitate with petroleum ether, and finally obtain a white solid powder, i.e. dopamine methacrylamide DMA, after vacuum drying the product.
[0071] Step 2: Under an inert gas atmosphere, 5 g of 2-ethyl-2-oxazoline, 1 g of methyl p-toluenesulfonate and 40 mL of anhydrous acetonitrile were added to the reaction bottle, placed in an 80°C oil bath, stirred for reaction for 12 h, then cooled to room temperature, 5.5 g of N-(3-dimethylaminopropyl) methacrylamide was added dropwise through a syringe, stirred for reaction at room temperature for 12 h, and the reaction was completed. The excess solvent was removed by a rotary evaporator, and the remaining product was precipitated with anhydrous ether and vacuum dried to obtain the final product, i.e., positively charged poly(2-ethyl-2-oxazoline) POX.
[0072] Step 3: Under an inert gas atmosphere, 0.1 g DMA and 0.4 g POX monomer were dissolved in 10 mL N,N-dimethylformamide (DMF), and 6 mg azobisisobutyronitrile (AIBN) was quickly added as an initiator. Stir at 70 ° C for 24 hours to allow the reaction to occur, and the viscosity change was observed during the reaction. After the reaction, the mixture was dialyzed with deionized water for 3 days and freeze-dried for 1 day to obtain the final product, DMA-POX.
[0073] Example 4
[0074] Step 1: Under an inert gas atmosphere, add 4g of sodium hydroxide, 10g of sodium tetraborate and 100mL of deionized water to a 250mL three-necked flask to fully dissolve them. At room temperature, quickly add 3g of dopamine hydrochloride, and at the same time, drop a mixed solution of 5mL of methacrylic anhydride and 25mL of tetrahydrofuran into a round-bottom flask, and then adjust the pH value of the solution to 8.5 with sodium hydroxide. At the same time, monitor the pH value of the solution every 2h to control it at 8.5. After reacting at room temperature for 12h, adjust the pH of the reaction mixture to 2 with hydrochloric acid. After the reaction is complete, extract with ethyl acetate, dry with anhydrous magnesium sulfate, precipitate with petroleum ether, and finally obtain a white solid powder, i.e. dopamine methacrylamide DMA, after vacuum drying the product.
[0075] Step 2: Under an inert gas atmosphere, 5 g of 2-ethyl-2-oxazoline, 1 g of methyl p-toluenesulfonate and 40 mL of anhydrous acetonitrile were added to the reaction bottle, placed in an 80°C oil bath, stirred for reaction for 12 h, then cooled to room temperature, 5.5 g of N-(3-dimethylaminopropyl) methacrylamide was added dropwise through a syringe, stirred for reaction at room temperature for 12 h, and the reaction was completed. The excess solvent was removed by a rotary evaporator, and the remaining product was precipitated with anhydrous ether and vacuum dried to obtain the final product, i.e., positively charged poly(2-ethyl-2-oxazoline) POX.
[0076] Step 3: Under an inert gas atmosphere, 0.3 g DMA and 1.2 g POX monomer were dissolved in 10 mL N,N-dimethylformamide (DMF), and 6 mg azobisisobutyronitrile (AIBN) was quickly added as an initiator. Stir at 70 ° C for 24 hours to allow the reaction to occur, and the viscosity change was observed during the reaction. After the reaction, the mixture was dialyzed with deionized water for 3 days and freeze-dried for 1 day to obtain the final product, DMA-POX.
[0077] Example 5
[0078] Step 1: Under an inert gas atmosphere, add 4g of sodium hydroxide, 10g of sodium tetraborate and 100mL of deionized water to a 250mL three-necked flask to fully dissolve them. At room temperature, quickly add 3g of dopamine hydrochloride, and at the same time, drop a mixed solution of 5mL of methacrylic anhydride and 25mL of tetrahydrofuran into a round-bottom flask, and then adjust the pH value of the solution to 8.5 with sodium hydroxide. At the same time, monitor the pH value of the solution every 2h to control it at 8.5. After reacting at room temperature for 12h, adjust the pH of the reaction mixture to 2 with hydrochloric acid. After the reaction is complete, extract with ethyl acetate, dry with anhydrous magnesium sulfate, precipitate with petroleum ether, and finally obtain a white solid powder, i.e. dopamine methacrylamide DMA, after vacuum drying the product.
[0079] Step 2: Under an inert gas atmosphere, 5 g of 2-ethyl-2-oxazoline, 1 g of methyl p-toluenesulfonate and 40 mL of anhydrous acetonitrile were added to the reaction bottle, placed in an 80°C oil bath, stirred for reaction for 12 h, then cooled to room temperature, 5.5 g of N-(3-dimethylaminopropyl) methacrylamide was added dropwise through a syringe, stirred for reaction at room temperature for 12 h, and the reaction was completed. The excess solvent was removed by a rotary evaporator, and the remaining product was precipitated with anhydrous ether and vacuum dried to obtain the final product, i.e., positively charged poly(2-ethyl-2-oxazoline) POX.
[0080] Step 3: Under an inert gas atmosphere, 0.5 g DMA and 2.0 g POX monomer were dissolved in 10 mL N,N-dimethylformamide (DMF), and 6 mg azobisisobutyronitrile (AIBN) was quickly added as an initiator. Stir at 70 ° C for 24 hours to allow the reaction to occur, and the viscosity change was observed during the reaction. After the reaction, the mixture was dialyzed with deionized water for 3 days and freeze-dried for 1 day to obtain the final product, DMA-POX.
[0081] Figure 1 is the DMA obtained in Example 5 1 H NMR spectroscopy, Figure 2 The POX obtained in Example 5 1 H NMR spectroscopy, Figure 3 is the DMA-POX obtained in Example 5 1 H NMR spectroscopy, Figure 4 This is the Fourier infrared spectrum of DMA obtained in Example 5, Figure 5 This is the Fourier infrared spectrum of POX obtained in Example 5, Figure 6 This is the Fourier infrared spectrum of DMA-POX obtained in Example 5. By comparing the infrared spectrum of the super-lubricating copolymer DMA-POX with that of the two reactants, it can be seen that DMA-POX has characteristic peaks of OH, C=O, NH and CN amide groups, as well as 3110 cm -1 The stretching vibration peak of Ar-H at 1370 cm-1 According to the above figure, it can be determined that the obtained product has the target structure.
[0082] Table 1 is a summary of the performance characterization results of the copolymers obtained in Examples 1-5
[0083]
[0084] Example 6
[0085] Step 1: Prepare a dual-channel microfluidic injection pump, the external phase is the continuous phase, add 5mL of liquid paraffin; the dispersed phase is 10wt% methacrylated gelatin solution and 0.5wt% LAP photoinitiator of methacrylated gelatin mass, respectively, place the syringes containing 5mL of aqueous solution and 5mL of oil phase solution horizontally on the micro-injection pump, and use a capillary to connect the needle to the inlet of the chip. Set the push speed, the aqueous channel speed is 1μL / s, and the oil channel speed is 5μL / s, start the device, under the shear force of the continuous phase, the dispersed phase solution will be sheared into dispersed droplets, and the droplets collected at the outlet pipe will be polymerized into microspheres after being exposed to UV light (365nm) for 20 seconds. The collected microspheres are washed three times with anhydrous ethanol and PBS to obtain gelatin microspheres (blank microspheres, i.e., GelMA microspheres).
[0086] Step 2: The DMA-MPC copolymer (4 mg / mL) prepared in Example 5 was dispersed in Tris-HCl buffer (pH=8.5, 1 M), and then 16 mg of gelatin microspheres were added to the above solution (4 mL). The mixture was shaken for 24 h in the dark and then rinsed with deionized water to obtain GelMA@DMA-POX lubricating microspheres. The surface charge of the microspheres was tested and Fourier infrared spectroscopy was used to characterize that the lubricating copolymer was successfully modified on the microsphere surface.
[0087] The surface charge test results of blank microspheres, super lubricating copolymers and lubricating microspheres are shown in Figure 7 As shown, according to Figure 7 The results show that the blank microspheres are negatively charged, and the superlubricating copolymer is positively charged due to the presence of positively charged poly(2-ethyl-2-oxazoline). The superlubricating microspheres are successfully modified with the copolymer and are positively charged. Figure 8 The Fourier transform infrared spectrum results show that the FT-IR of blank microspheres and lubricated microspheres are compared, 2923, 1640, 1548, 1100 cm -1 The peaks corresponding to the CH stretching vibration, C=O stretching vibration, NH vibration and CN stretching vibration on the amide group are shown in Figure 2. It can be clearly seen that the amide peak intensity of the lubricating microspheres is significantly higher than that of the blank microspheres, and the peak at 3200 cm -1 The OH stretching vibration peak is strong, which verifies that the superlubricating copolymer is successfully modified onto the surface of the microspheres.
[0088] Example 7
[0089] This example is an evaluation of the tribological properties of a biological superlubricating copolymer, and the preparation steps are as follows:
[0090] The friction coefficient test was performed using phosphate buffered saline (PBS), blank microspheres (10 mg / mL), and superlubricating microspheres (10 mg / mL) prepared in Example 6 as the test samples. The tribological test was performed using a universal material tester in reciprocating mode, with PBS as the control group, and each group of tests was repeated three times to ensure the accuracy of the data.
[0091] The friction coefficient test results are as follows: Fig. 9 As shown, according to Fig. 9 It can be seen from the results that compared with the PBS group, the friction coefficients of GelMA microspheres and DMA-POX-modified GelMA microspheres were reduced. Among them, the microspheres modified with DMA-POX had better lubrication properties, and the friction coefficient was reduced to about 0.018, which was 40% lower than that of the PBS group and 33% lower than that of the GelMA group.
[0092] Example 8
[0093] This example is a rat animal osteoarthritis treatment validation
[0094] First, 6-week-old male SD rats were used to establish an OA model: after the rats were anesthetized by intraperitoneal injection, they were fixed in a supine position, the hair of the knee joint was shaved, and the skin around the knee joint was disinfected with povidone-iodine solution. Under sterile conditions, a small incision was made on the inner side of the knee joint, and the subcutaneous tissue and muscle layer were cut layer by layer. After exposing the joint cavity, the anterior cruciate ligament of the knee joint was transected and the medial meniscus was removed, and then the rat joint cavity was closed and sutured layer by layer. In the sham operation group, only the muscle layer was cut to expose the joint cavity, and no other operations were performed. After surgery, 50,000 to 100,000 units of antibiotic penicillin sodium were injected daily for three days to prevent wound infection. Four weeks after the operation, the rats were randomly divided into 4 groups (n=6 in each group): sham operation group (Sham), model group (PBS), GelMA treatment group and GelMA@DMA-POX treatment group. Every 2 weeks, 150 μL PBS was injected into the joint cavity of the model group rats; 150 μL of GelMA blank microspheres and GelMA@DMA-POX lubricating microspheres in Example 6 were injected into the lubricant treatment group. The treatment course lasted for eight weeks. After the treatment, the knee joints were removed for radiographic examination and histological evaluation.
[0095] Fig.10 The therapeutic effects of PBS, GelMA blank microspheres and GelMA@DMA-POX lubricated microspheres on osteoarthritis rats. Fig.10The results showed that in the normal group, the surface of articular cartilage was smooth and intact; in the modeling group, synovial hyperplasia infiltrated into the joint cavity, the cartilage surface was severely defective, the subchondral bone was damaged, the chondrocytes and ECM were destroyed, and the staining was reduced. There was no significant difference between the GeMA group and the PBS group. In contrast, the cartilage destruction in the GelMA@DMA-POX lubricating microsphere group was improved to varying degrees, and the depth of cartilage erosion was significantly reduced. According to the results of safranin staining, the deposition of glycosaminoglycans was analyzed, showing that the GelMA@DMA-POX lubricating microsphere group had the highest content of glycosaminoglycans (GAG), and the progression of osteoarthritis was inhibited.
[0096] Fig.11 Micro-CT test results of PBS, GelMA blank microspheres and GelMA@DMA-POX lubricated microspheres on osteoarthritis rats. Fig.11 The results showed that compared with the smooth bone joints of the normal group, the modeling group had the most severe osteoarthritis symptoms, the most osteophytes were formed and the volume was the largest, and the subchondral bone was severely damaged and had bone defects. There was no significant difference between the blank microsphere GelMA group and the modeling group. In the microsphere treatment group with lubricating copolymer, the volume of osteophytes was significantly reduced, the subchondral bone defects were reduced, and it had the best inhibitory effect on osteoarthritis.
[0097] The results of the above examples show that the present invention selects methacrylic anhydride-modified dopamine with adhesion properties and poly (2-ethyl-2-oxazoline) with excellent hydration lubrication properties to synthesize super-lubricating copolymer materials through molecular structure design, effectively forming a lubricating layer, reducing friction and wear on the bone joint surface, and thus providing a lubricating effect. The super-lubricating copolymer modified with gelatin microspheres has lubricating properties that can reduce friction between bones and cartilage and relieve pain and discomfort caused by arthritis. The DMA-POX lubricating copolymer provided by the present invention is a new type of biological lubricating material and has broad application prospects in the treatment of osteoarthritis.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. Therefore, the protection scope of this patent application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A bone and joint biological super lubricating copolymer, characterized in that: The copolymer is prepared by free radical polymerization of dopamine methacrylamide with adhesiveness and poly (2-ethyl-2-oxazoline) with positive charge. The structural formula of the biological super-lubricating copolymer is shown in Formula I: In formula I: x=8~9, y=6~7.
2. The bone joint biological super lubricating copolymer according to claim 1, characterized in that: The preparation method of dopamine methacrylamide is as follows: sodium tetraborate and sodium hydroxide solution are mixed under nitrogen protection, dopamine hydrochloride is added at room temperature, and a mixed solution of methacrylic anhydride and tetrahydrofuran is dripped into the mixture to carry out grafting reaction to obtain dopamine methacrylamide.
3. The bone joint biological super lubricating copolymer according to claim 2, characterized in that: The mass ratio of dopamine hydrochloride to sodium tetraborate is 1:2-5, the volume ratio of methacrylic anhydride to tetrahydrofuran is 1:2-8, the grafting reaction temperature is 20-30°C, the reaction time is 12-24h, and the pH needs to be controlled at 2-3.
4. The bone joint biological super lubricating copolymer according to claim 1, characterized in that: The preparation method of the positively charged poly(2-ethyl-2-oxazoline) is as follows: 2-ethyl-2-oxazoline is mixed with an acetonitrile solution, and methyl p-toluenesulfonate and N-(3-dimethylaminopropyl)methacrylamide are added to carry out a grafting reaction to obtain the positively charged poly(2-ethyl-2-oxazoline).
5. The bone joint biological super lubricating copolymer according to claim 4, characterized in that: The mass ratio of 2-ethyl-2-oxazoline to methyl p-toluenesulfonate is 5-15:1, and the molar ratio of methyl p-toluenesulfonate to N-(3-dimethylaminopropyl)methacrylamide is 1:1-20; the temperature of the grafting reaction is 60-80°C, and the reaction time is 12-24h.
6. A method for preparing a bone joint biological super lubricating copolymer as claimed in claim 1, characterized in that: The preparation method comprises the following steps: mixing dopamine methacrylamide and positively charged poly (2-ethyl-2-oxazoline) with N,N-dimethylformamide solvent, and performing free radical polymerization to obtain a biological super-lubricating copolymer.
7. The method for preparing the bone and joint biological super lubricating copolymer according to claim 6, characterized in that: The mass ratio of the dopamine methacrylamide to the positively charged poly (2-ethyl-2-oxazoline) is 1:1-10, the reaction temperature of the free radical polymerization reaction is 60-80° C., and the time is 12-48 hours.
8. A bone and joint biological super lubricating copolymer solution, characterized in that: The copolymer solution is prepared by dissolving the copolymer as claimed in claim 1 in a good solvent to obtain a bone and joint biological super-lubricating copolymer solution.
9. The bone and joint biological super lubricating copolymer solution according to claim 8, characterized in that: The good solvent is Tris-HCl buffer; the concentration of the bone and joint biological super-lubricating copolymer in the solvent is 1-10 mg / mL.
10. A bone-articular biological super-lubricating copolymer or a bone-articular biological super-lubricating copolymer solution as claimed in claim 1 or 8 for preparing pharmaceutical microspheres for treating osteoarthritis.
Citation Information
Patent Citations
Silicone hydrogels with amino surface groups
CN101835846A
Novel isoxazolines as antiinflammatory agents
CN1091132A
Responsive release lubricating carrier as well as preparation method and application thereof
CN114931639A
Multifunctional nano-material with lubricating and targeting effects as well as preparation method and application of multifunctional nano-material
CN118453885A